Eyemaginary unity: a dialectic of visual studies. Issue 4 (7th August 2020) - O'Sullivan, Luke
Abstract : The late twentieth century visual turn established the study of visual culture as central to the humanities and social sciences. Yet there is no consensus over the scope of the field that has come to be known as visual studies. This article offers a dialectical account in response. It finds a precedent in two dialectical models that have been prominent in visual studies, namely those of Walter Benjamin and Maurice Merleau-Ponty. It argues that the work of Merleau-Ponty offers the better model for a contemporary dialectic because it is not tied to a particular ideological position. Merleau-Ponty's work can be used to ground a dialectic of visual culture which begins with the eye and has as its three main moments the life-world, representation, and technology. Each of these three moments is explored in turn in order to demonstrate that this is a genuine dialectic in the sense that the final stage returns to the initial position but leaves it thoroughly transformed. The advantage of this approach is that it yields, for the first time, an account of the study of visual culture that does not rely on ideological or methodological principles to explain the range of the field.